Synthesis, Structural, Electrical, and Thermal Studies of Pb1-xBaxNb 2O 6 (x=0.0 and 0.4) Ferroelectric Ceramics. (5th September 2012) - Barbar, Shiv K.; Roy, M.
Abstract : The polycrystalline ceramic samples of lead barium niobate with general formula Pb 1-x Ba x Nb 2 O 6 (x = 0.0 and 0.4) were prepared by conventional solid state reaction method. The room temperature X-ray diffraction patterns reveal that both of the samples have orthorhombic crystal structure with space group Cm2m. The dielectric constant and dissipation factor were measured as a function of frequency (100 Hz-2 MHz) and temperature (RT-660K). The DC electrical conductivity of both the samples was measured from RT to 660 K. The activation energies calculated from log σ versus 1000/ T curves in ferroelectric phase of the compounds are 1.09 eV for pure (x = 0.0 ) sample and 1.36 eV for Ba-substituted (x = 0.4 ) sample. The values of activation energies show that the substitution of Ba 2+ ion on Pb 2+ ion site increases the resistivity of pure PbNb2 O6 (x = 0.0 ) ceramic. The modulated differential scanning calorimetry (MDSC) has been used to investigate the phase transition temperature of both the compounds and also to see the effect of Ba 2+ ion substitution on the phase transition temperature, specific heat, and other thermal parameters of the compound.